2008
DOI: 10.1016/j.jacc.2008.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of the Sodium-Iodide Symporter Enables Imaging of Transplanted Cardiac Stem Cells In Vivo by Single-Photon Emission Computed Tomography or Positron Emission Tomography

Abstract: Objectives We examined the sodium-iodide symporter (NIS) which promotes in vivo cellular uptake of 99mTc or 124I, as a reporter gene for cell tracking by SPECT or PET imaging. Background Stem cells offer the promise of cardiac repair. Stem cell labeling is a prerequisite to tracking cell fate in vivo. Methods The human NIS cDNA was transduced into rat cardiac-derived stem cells (rCDCs) using lentiviral vectors. Rats were injected intra-myocardially with up to 4 million NIS+-rCDCs immediately following LAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(153 citation statements)
references
References 27 publications
4
148
0
Order By: Relevance
“…NIS overexpression was also reported for several nonthyroidal cancer types including colorectal, lung, and a subset of breast cancers (13,(20)(21)(22)(23)(24), but it remains to be determined if those NIS expression levels are sufficient and consistent enough for accurate diagnosis and therapy. NIS has also been used as a reporter gene preclinically in cardiac (25), hematopoietic (26), and neural studies (27); for tracking macrophage migration (28); and for noninvasive imaging of gene therapy vectors (29,30). It has not yet been used for cancer metastasis tracking.…”
mentioning
confidence: 99%
“…NIS overexpression was also reported for several nonthyroidal cancer types including colorectal, lung, and a subset of breast cancers (13,(20)(21)(22)(23)(24), but it remains to be determined if those NIS expression levels are sufficient and consistent enough for accurate diagnosis and therapy. NIS has also been used as a reporter gene preclinically in cardiac (25), hematopoietic (26), and neural studies (27); for tracking macrophage migration (28); and for noninvasive imaging of gene therapy vectors (29,30). It has not yet been used for cancer metastasis tracking.…”
mentioning
confidence: 99%
“…NIS genes can be used as imaging reporter genes in PET as well as SPECT imaging, because they concentrate radionuclides such as 124 I, 131 I, and 99m Tc-pertechnetate, which can be visualized by conventional γ-camera or PET [64][65][66]. Terrovitis et al showed that NIS-expressing (NIS + ) rat cardiac-derived stem cells (rCDCs) were visualized in vivo up to 6 days post-injection in a rat MI model by SPECT [67]. Lee et al showed that intramyocardially injected rats with NIS-expressing adenovirus-transfected canine stem cells (Ad-hNIS-canine ADSCs) were monitored for 9 days in the canine MI model by 99m Tc-pertechnetate ( 99m TcO4 − ) SPECT imaging (Fig.…”
Section: Indirect Labelingmentioning
confidence: 99%
“…The final obstacle is the inadequate conditions for engraftment since there is no pre-established vasculature present to nourish the transplanted cells (Martens, et al, 2009). In some cases, there will be little or no space for the cells to divide into since the target tissue has no cavity (Darabi, et al, 2009;Laflamme, et al, 2007;Terrovitis, et al, 2008). It is no surprise that most transplanted cells die within 24 hours of transplantation (Bliss, et al, 2007;Guerette, et al, 1997;Snyder, et al, 2010;Suzuki, et al, 2004;Tate, et al, 2009;Terrovitis, et al, 2008;Zhong, et al, 2010 (Kaihara and Vacanti, 1999).…”
Section: Challenges For Novel Stem Cell-based Therapiesmentioning
confidence: 99%
“…In short, the transplanted stem cells need help to stay alive long enough for their therapeutic effect to be seen. The majority of stem and progenitor cells in the transplanted bolus die shortly after transplantation (Bliss, et al, 2007;Snyder, et al, 2010;Terrovitis, et al, 2008;Zhong, et al, 2010). In some cases, more than 95% of transplanted stem cells die within two weeks of transplantation (Snyder, et al, 2010;Terrovitis, et al, 2008;Zhong, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation